2013
DOI: 10.1088/0004-637x/775/2/126
|View full text |Cite
|
Sign up to set email alerts
|

LoCuSS: THE STEADY DECLINE AND SLOW QUENCHING OF STAR FORMATION IN CLUSTER GALAXIES OVER THE LAST FOUR BILLION YEARS

Abstract: We present an analysis of the levels and evolution of star formation activity in a representative sample of 30 massive galaxy clusters at 0.15 Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

28
142
0

Year Published

2015
2015
2016
2016

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 131 publications
(170 citation statements)
references
References 147 publications
(196 reference statements)
28
142
0
Order By: Relevance
“…Figure 6 shows the comparison of the Guo et al (2014) IR LF in groups at z < 0.1 with the IR LF of the Shapley supercluster studied in Haines et al (2010), which as shown in Haines et al (2013), is consistent with the IR LF of the Coma cluster and A3266 studied by Bai et al (2006) and Bai et al (2009), respectively. Our IR LF in groups at 0.1 < z < 0.4 is compared with the stacked IR LF of 30 clusters observed at 0.15 < z < 0.30 in the LoCuSS survey (Haines et al 2013). Our IR LF in groups at 0.4 < z < 0.8 is compared with the stacked IR LF of six rich clusters at 0.6 < z < 0.8 studied in Finn et al (2010).…”
Section: The Composite Lf: Resultssupporting
confidence: 80%
See 2 more Smart Citations
“…Figure 6 shows the comparison of the Guo et al (2014) IR LF in groups at z < 0.1 with the IR LF of the Shapley supercluster studied in Haines et al (2010), which as shown in Haines et al (2013), is consistent with the IR LF of the Coma cluster and A3266 studied by Bai et al (2006) and Bai et al (2009), respectively. Our IR LF in groups at 0.1 < z < 0.4 is compared with the stacked IR LF of 30 clusters observed at 0.15 < z < 0.30 in the LoCuSS survey (Haines et al 2013). Our IR LF in groups at 0.4 < z < 0.8 is compared with the stacked IR LF of six rich clusters at 0.6 < z < 0.8 studied in Finn et al (2010).…”
Section: The Composite Lf: Resultssupporting
confidence: 80%
“…The group galaxy IR LF shows a smoother decline at high luminosity which is more consistent with a Schechter or a modified Schechter function than with a double power law. The double power law predicts too many bright galaxies at the bright end, especially in the two lowest redshift bins, where we observe a rather fast decline of the LF Saunders et al (1990) for the composite IR LF of our group sample, the local mean IR LF derived from the work of Guo et al (2014), and for the cluster IR LF of Haines et al (2013), respectively.…”
Section: The Composite Lf: Resultsmentioning
confidence: 59%
See 1 more Smart Citation
“…It is also supported by the observations of several clusters at intermediate redshift (e.g. Haines et al 2013Haines et al , 2015. In its current form, however, this scenario over-predicts the number of red dwarf galaxies compared to what is observed in nearby clusters (Kang & van den Bosch 2008;Font et al 2008;Kimm et al 2009;De Lucia 2011;Weinmann et al 2011;Taranu et al 2014).…”
Section: Introductionsupporting
confidence: 61%
“…At low redshift, it has been argued that environmental processes shut down star formation in satellites over a long timescale of ∼2-7 Gyr in order to explain the distribution of satellite quiescent fractions (e.g., Balogh et al 2004;Finn et al 2008;Weinmann et al 2009;McGee et al 2011;De Lucia et al 2012;Haines et al 2013;Wetzel et al 2013). The reduced quenching of satellites at higher redshifts (Figure 7) is therefore expected, since satellites will not have had time to quench; however, these timescales are still too long to explain the existence of quenched satellites at these higher redshifts.…”
Section: Physical Causes Of Conformitymentioning
confidence: 99%